1993
DOI: 10.2165/00002512-199303020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre Study of l-??-Glyceryl-Phosphorylcholine vs ST200 among Patients with Probable Senile Dementia of Alzheimer??s Type

Abstract: A multicentre, randomised, controlled study compared the efficacy of l-alpha-glyceryl-phosphorylcholine (alpha GPC) and ST200 (acetyl-l-carnitine) among 126 patients with probable senile dementia of Alzheimer's type (SDAT) of mild to moderate degree. Efficacy was evaluated by means of behavioural scales and psychometric tests. The results showed significant improvements in most neuropsychological parameters in the alpha GPC recipients. Improvements also occurred in the ST200 recipients but to a lesser extent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
2
20
0
2
Order By: Relevance
“…It cannot be excluded that similarly as observed in the above models, neuroprotective activity of galantamine in our experimental model is related to up-regulation of the protective protein Bcl-2 and is mediated via alpha-7 nAChR [11]. The other compound investigated, choline alphoscerate, is a choline-containing phospholipids extensively studied in preclinical settings both in vitro and in vivo [14,15,[33][34][35][36][37][38][39]. Choline alphoscerate is probably, among choline-containing phospholipids, the most effective in enhancing in vivo acetylcholine release [33] and was also investigated with positive results on cognitive domain in patients affected by cerebrovascular disorders and VaD [14][15][16][17].…”
Section: Discussionsupporting
confidence: 58%
“…It cannot be excluded that similarly as observed in the above models, neuroprotective activity of galantamine in our experimental model is related to up-regulation of the protective protein Bcl-2 and is mediated via alpha-7 nAChR [11]. The other compound investigated, choline alphoscerate, is a choline-containing phospholipids extensively studied in preclinical settings both in vitro and in vivo [14,15,[33][34][35][36][37][38][39]. Choline alphoscerate is probably, among choline-containing phospholipids, the most effective in enhancing in vivo acetylcholine release [33] and was also investigated with positive results on cognitive domain in patients affected by cerebrovascular disorders and VaD [14][15][16][17].…”
Section: Discussionsupporting
confidence: 58%
“…The possible CNS actions of acetyl‐L‐carnitine have been thoroughly reviewed 96 . Although some studies disagree, 97,98 acetyl‐L‐carnitine has been shown to slow the progression of symptoms in AD and to produce few and mild side effects 99,100 …”
Section: Resultsmentioning
confidence: 99%
“…The use of CDP-choline in cognitive decline (vascular or degenerative) improved some neuropsychological and/or cognitive tests such as Mini Mental State Examination (MMSE) and Alzheimer ' s Disease Assessment Scale-cognitive (ADAS-cog) [ 77 ]. In 1993, a multicenter study showed that GPC treatment improved most neuropsychological parameters in elderly patients with probable dementia [ 63 ]. Ten years later, the effect of GPC was studied in a multicenter, double-blind, randomized, placebo-controlled trial, patients affected by mild to moderate dementia of the Alzheimer ' s type [ 78 ].…”
Section: Treatment With Cdp-choline and Gpc: Pre-clinical And Clinicamentioning
confidence: 99%